Aplikasi Thread ”Fomo” Sebagai Budaya Imitasi dalam prespektif Studi Etnografi - Iin Soraya (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
The initial launch of Threads in Indonesia was proven to have reached 100 million users, many of whom downloaded the Threads application among Gen Z or teenagers who initially used Instagram, then downloaded the application and became Threads users. This is done just to join in, and not be left behind by other Instagram users. This kind of behavior is now known as Fear of Missing Out (FoMO). FoMO can be said to be a form of anxiety characterized by the desire to always know what other people are doing, as well as the fear of missing out on trends if you don't follow something that is viral, so this has given rise to a culture of imitation in generation Z. This research aims to find out Application of the